(untitled) (Global Journal of Medical Research, 2022)
Brunner gland lesions BGL encompass benign proliferations of the homonymous glands and have been designated as hyperplasia adenoma BGA hamartoma or nodule In general terms lesions larger than 0 5 cm are considered true neoplasia with an unknown malignant potential and unclear pathogenesis Genetic alterations have seldom been reported in BGL and include SMAD4 DPC4 and LRIG1 but not KRAS to the best of our knowledge We present a 64-year-old man evaluated for iron deficiency anemia harboring a 1 5 cm BGA found by duodenoscopy Immunohistochemistry failed to reveal microsatellite instability and next generation sequencing revealed a KRAS G12D point mutation